COMPARATIVE STUDY ON CHARAKA NIDANA STHANA WITH OTHER CLASSICS - Shashirekha, H. K.; Sushant Sukumar, Bargale (International Journal of Ayurveda and Pharma Research, 2015)
Among all the available classics, the most ancient representative of Kaya Chikitsa is Charaka Samhita. It is not only a text book it is an ideal ancient treatise based on eternal fundamentals and basic principles. Charaka Samhita consists of eight diseases in Nidana Sthana. All the classics gives importance to Nidana because it is a Sarva Tantra Siddantha that, the effect will always going to imitate the cause i.e. Karya Karana Bhava. Before understanding Chikitsa the knowledge of nidana is very necessary and for all disease. The main line of treatment is Nidana parivarjana and to get the clear knowledge of disease one should know about the Nidana panchaka, which is explained in Nidana sthana. Diagnosis is never complete without the elicitation of all the factors associated with the diseases. Aims and Objectives: To enlighten the basic concept of framework of Nidana sthana to its full perspective and the importance to the specific concept as well as the number of chapter given in Nidana sthana. Materials and Methods: In this study classical Ayurveda text were thoroughly studied where the compilation has been done. Discussion: compiled all the information of Nidana sthana and critically analysed in aspect of content and chapters of each Nidana sthana of different classics. Elicitation of Nidana is necessary for the proper identification of Dosha, the Roga, Rogavasta, Roga Bala, and Sadhya Asadhya. Result: Charaka nidana sthana is provides the basic fundamental concept to all other classics. Nidana sthana gives the draft of many pathogenesis. The other classics elaborated the Nidana panchaka concept in very detail manner.